Annual report of the Director of the Mint : fiscal year ended June 30, 1976 and transition quarter Department of the Treasury Bureau of the mint (Washington, D.C. : Dept. of the Treasury, Bureau of the Mint : For sale by the Supt. of Docs., U.S. G.P.O., 1977)
This report is submitted in compliance with section 345 of the Revised Statutes of the United States, 2nd Edition (1878), 31 U.S.C. 253. It includes a review of the operations of the mints, assay offices, and bullion depositories for the fiscal year ended June 30, 1976, and the transition quarter, July to September 1976.
osc 10/04/2019
Ref.
Keywords: Mints; Coinage; United States